Adverse Events Associated With Image‐Guided Sinus Navigation in Endoscopic Sinus Surgery: A MAUDE Database Analysis. (27th January 2023) - Reyes Orozco, Francis; Ulloa, Ruben; Lin, Matthew; Xepoleas, Meredith; Paoletti, Marcus; Liu, Xuan; Hur, Kevin
Abstract: Objective: The utilization of image‐guided navigation during endoscopic sinus surgery (ESS) has increased significantly since its introduction. However, the most common associated complications are still unknown. This study describes and analyzes adverse events related to image‐guided ESS. Study Design: Cross‐sectional analysis. Setting: The Food and Drug Administration's 2018‐2022 MAUDE database (Manufacturer and User Facility Device Experience). Methods: The MAUDE database was searched for all reports on adverse events involving sinus navigation systems used in ESS from 2018 to 2022. Reported events were reviewed and categorized. Results: During the study period, there were 1857 adverse events from 1565 reports, which were divided into device‐related (n = 1834, 98.8%) and patient‐related (n = 23, 1.2%) complications. The most common device‐related complications were nonfunctionality of the system (n = 512, 27.9%), device imprecision (n = 427, 23.3%), and device sensing problems (n = 277, 15.1%). The most common patient‐related complications were cerebrospinal fluid (CSF) leak (n = 14, 60.9%), intracranial injury (n = 4, 17.4%), and bleeding/hemorrhage (n = 3, 13.1%). Imprecision was associated with increased risk of navigation abortion by the surgeon (odds ratio, 1.50 [95% CI, 1.38‐1.65]; P < .001) and increased risk of CSF leak (odds ratio, 16.5 [95% CI, 3.66‐74.0]; P < .001) as compared with other device‐related complications. Conclusions: The most commonly reported device‐ and patient‐related adverse events associated with image‐guided sinus navigation systems were device nonfunction, imprecision, device sensing difficulties, and CSF leak. When imprecise navigation occurred, there was an increased likelihood of CSF leak and navigation abortion by the surgeon. Health care providers should be mindful of these possible complications when electing to use image‐guided sinus navigation during ESS.